Toxoplasma gondii infection among selected indigenous community in Sarawak, East Malaysia - Romano, Ngui; N.A, Hassan; Chang, L. Y.; Teh, S.J.C; Chua, K. H.; Kee, B. P.; Hoe, S .Z; Lim, Y.A.L. (Malaysian Society of Parasitology and Tropical Medicine, 2020)
Toxoplasma gondii is an obligate intracellular protozoan parasite that causes toxoplasmosis in humans. To date, little is known about T. gondii infection among the indigenous community, particularly in East Malaysia. This study was conducted to determine the status of T. gondii infection and to investigate associated risk factors among the indigenous community of Sarawak, East Malaysia. The sociodemographic data was obtained using a pretested questionnaire. A serological test was done to detect the presence of specific IgM and IgG antibodies against T. gondii in serum samples. A nested polymerase chain reaction (PCR) was used to determine acute infection among seropositive individuals. The overall seroprevalence of T. gondii infection was 50% (95% CI = 43.3 – 56.7). From this subset, 40.1%, 5.7%, and 4.2% were positive for anti-T. Gondii IgG antibodies, IgM, and both IgG and IgM, respectively. Four seropositive samples were amplified through PCR. None of the pregnant women tested positive for T. gondii infection based on the serological and PCR assays. A significant association was found between age, low monthly household income, unemployment, usage of untreated water and close contact with T. gondii seropositive cats. These results provide basic information on T. gondii infection and may be useful for policymakers to initiate prevention and control programs, especially amongst pregnant women and women of childbearing age in the indigenous community.